Biomarkers of immunotherapy response in patients with allergic rhinitis. (3rd August 2018) - Licari, Amelia; Castagnoli, Riccardo; Brambilla, Ilaria; Tosca, Maria Angela; De Filippo, Maria; Marseglia, Gianluigi; Ciprandi, Giorgio
ABSTRACT: Introduction : Allergen immunotherapy represents the only disease-modifying therapy available for immunoglobulin E-mediated diseases such as allergic rhinitis and asthma. Allergen immunotherapy induces allergen tolerance by interfering with the immune-pathogenic mechanisms of the allergic response and is potentially able to provide long-term relief of symptoms of allergic rhinitis and asthma and alter the natural course of allergic diseases. Areas covered : Since allergen immunotherapy (AIT) is actually considered an individualized treatment on patient's clinical and immunological profile, the identification of specific biomarkers, which may guide diagnosis, management, and predict response to AIT treatment in allergic rhinitis (AR) patients, is essential and is currently an active field of research. Expert commentary : The identification and validation of biomarkers of successful AIT for AR is an urgent need to definitively establish the role of AIT as a therapeutic tool of personalized medicine.